CROISSANCE DE CYPRINUS CARPIO LINNAEUS, 1758 (CYPRINIDAE) DANS LE BARRAGE EL K'SOB DANS LA WILAYA DE M'SILA (ALGÉRIE) - MIMECHE, FATEH; BELHAMRA, MOHAMMED; MIMECHE, HAYET (Courrier du Savoir; Vol. 19 (2015): COURRIER DU SAVOIR(Mars), 2015)
ABSTRACT In the present study, sex, some biometric measurements, relationship length-weight and condition factor were examined in 150 specimens of Cyprinus carpio L. 1758 (common carp) captured in the K’sob reservoir (M’Sila, NE of Algeria) from January to June 2013. The overall male to female ratio was 1: 0.24 (Chi-square X2 = 16.96, P = 0.0019). The maximum lengths were observed is 38.0 cm in females and 30.0 cm in males. Comparing the values of the slope of the regression lines to the unit by the "t" test of Student for both sexes has shown the existence of a significant difference for some characters; LS isometric in females, minorant allometry in males; LF isometric for both sexes; HB minorant allometry in males, isometric in females and PD allometry minorant for both sexes. The relation between (LT -WT) and (FL - EW) of the carp shows that the exponent b is between 2.52 and 2.69.The mean condition factor was 0.961 ± 0.229 (±IC). KEYWORDS: Cyprinus carpio, sex, growth, condition factor, K’sob reservoir.